Existence and stability results for $ψ$-Caputo fractional integrodifferential equations with delay - D, Prabu (Hilbert Journal of Mathematical Analysis, 2024)
This paper deals with the existence and uniqueness results for $ψ$-Caputo fractional integrodifferential equations with finite delay. The results are obtained by using the standard fixed point theorems. An example is given to show the main discoveries.